Mitochondrial Genomes of Four Millipedes (Diplopoda: Spirostreptida and Spirobolida) Unveil Phylogenetic Novelty and Gene Rearrangement Patterns - Yingzhu Li; Gaoji Zhang; Wei Xu; Tangjun Xu; Lingna Li; Ming Gao; Jiachen Wang; Hongyi Liu (Current Issues in Molecular Biology)
Millipedes (Diplopoda) are crucial decomposers in soil ecosystems, as they play a vital role in organic matter degradation while also holding potential as bioindicators of environmental health. This study deciphered the complete mitogenomes of four millipede species (Diplopoda: Spirostreptida and Spirobolida) using next-generation sequencing technology, thus revealing evolutionary relationships among diplopod taxa and characterizing mitochondrial genomic features. The full mitochondrial sequences of Agaricogonopus acrotrifoliolatus, Bilingulus sinicus, Paraspirobolus lucifugus, and Trigoniulus corallinus, ranged in size from 14,906 to 15,879 bp, with each containing 37 typical genes and one D-loop region. Notably, the D-loop regions of A. acrotrifoliolatus and B. sinicus were positioned atypically, thus indicating structural rearrangements. A nucleotide composition analysis revealed pronounced AT-skews, with tRNA sequences exhibiting the highest A+T content. Ka/Ks ratios demonstrated that the ND5 gene experienced the weakest purifying selection pressure, thus suggesting its potential role in adaptive evolution. The results of the phylogenetic analysis showed genetic relationships between the three orders of ((Julida, Spirostreptida), Spirobolida), which was inconsistent with the previous conclusion regarding the three orders, obtained through morphological studies: ((Julida, Spirobolida), Spirostreptida). These findings highlight the role of the mitochondrial genome in resolving phylogenetic conflicts and provide important insights for further studies on millipedes.